2005
DOI: 10.4992/jjpsy.76.227
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hope and subjective well-being: Reliability and validity of the dispositional Hope Scale, Japanese version

Abstract: We conducted three studies to translate the Snyder Hope Sales into Japanese, examine reliability and validity of the Japanese version, and investigate the relationship between the tendency to be hopeful and subjective well-being. In Study 1, confirmatory factor analysis was performed of the Hope Scale in the Japanese version: agency and pathways. Its test-retest reliability coefficients for the data from 113 undergraduates ranged from .81 to .84. In Study 2, concurrent validity of the Japanese version Hope Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 0 publications
4
34
1
2
Order By: Relevance
“…people having high level of hope are mentally more healthy than others. Kato and Synder (2005) witnessed to the fact that hope and subjective well-being were positively related and hope had negative correlations with stress response, hopelessness, depressive tendency, and trait anxiety, but possess positive correlation with feeling of happiness. Further it has been also observed from prior evidences that SWB has inversely related with negative emotions.…”
Section: International Journal Of Research Studies In Psychology 37mentioning
confidence: 99%
“…people having high level of hope are mentally more healthy than others. Kato and Synder (2005) witnessed to the fact that hope and subjective well-being were positively related and hope had negative correlations with stress response, hopelessness, depressive tendency, and trait anxiety, but possess positive correlation with feeling of happiness. Further it has been also observed from prior evidences that SWB has inversely related with negative emotions.…”
Section: International Journal Of Research Studies In Psychology 37mentioning
confidence: 99%
“…Hope is a fundamental emotion for understanding basic human responses, such as goal setting, investment, coping, change, and purchase‐related decision‐making (MacInnis and De Mello ). Hope is defined as a construct that involves an individual's willingness to pursue goals (i.e., agency) and strategies to identify ways to meet goals (i.e., pathways) (Feldman and Kubota ; Kato and Snyder ; Yavas, Karatepe, and Babakus ). Thus, hope is conceptualized in a goal‐setting framework, where hopeful individuals determine what they wish to achieve and how to achieve it (Snyder ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Finally, in a study of 1,031 multiethnic adults, Roesch and Vaughn (2006) sought to test the factorial validity and structure of the Hope Scale and found invariance across ethnic groups as well as support for the two-factor model of hope. The Adult Dispositional Hope Scale has been translated into several languages, including Arabic (Abdel-Khalek & Snyder, 2007), Chinese (Sun, Ng, & Wang, 2012), Dutch (Brouwer, Meijer, Weekers, & Baneke, 2008), French (Gana, Daigre, & Ledrich, 2013), Japanese (Kato & Snyder, 2005), Portuguese (Marques, Lopez, Fontaine, Coimbra, & Mitchell, 2014;Pacico, Bastianello, Zanon, & Hutz, 2013), Slovak (Halama, 1999(Halama, , 2001, and Spanish (Galiana, Oliver, Sancho, & Tomás, 2015). Of the studies noted previously, several (Galiana et al, 2015;Gana et al, 2013;Marques et al, 2014;Pacico et al, 2013;Sun et al, 2012) used the process of translation and back translation as first steps toward establishing linguistic equivalence.…”
Section: Adult Dispositional Hope Scalementioning
confidence: 99%
“…Support for construct equivalence (e.g., the two-factor structure of hope) was found in samples in China (Sun et al, 2012), France (Gana et al, 2013), Japan (Kato & Snyder, 2005), and Portugal (Marques et al, 2014). In contrast, studies in Brazil (Pacico et al, 2013), Spain (Galiana et al, 2015), and the Netherlands (Brouwer et al, 2008) found that hope was better conceptualized as one factor (Rand & Touza, 2016).…”
Section: Studies Of Equivalence Of the Adult Dispositional Hope Scalementioning
confidence: 99%